Evaluating Craniofacial Morphology Ratios as Predictors of Obstructive Sleep Apnea Severity in Non-Obese Adult Males - Masasuke Shimatsu; Shigeto Kawashima; Mitsuyoshi Suzuki (Dentistry Journal)
Background: This study aimed to examine the connection between craniofacial morphology, particularly the horizontal and vertical dimensions of the mandible, and the severity of obstructive sleep apnea (OSA) in non-obese adult males by utilizing a cephalometric analysis and introducing a new skeletal ratio index. Methods: A cohort of 44 non-obese adult males with OSA, diagnosed via the apnea–hypopnea index (AHI) from polysomnographic recordings, was evaluated using a lateral cephalometric analysis. OSA severity was classified as mild (5 ≤ AHI < 15) in 19 patients, moderate (15 ≤ AHI < 30) in 15 patients, and severe (AHI ≥ 30) in 10 patients. The S-Go distance divided by the N-Me distance (S-Go/N-Me) was used as a vertical ratio of craniofacial morphology, the Go-Me distance divided by the S-N distance (Go-Me/S-N) was used as a horizontal ratio, and the results were compared between groups. Correlations between each ratio and craniofacial morphology based on the five factors from the Ricketts analysis were examined for each group. Results: A significant difference was found in the horizontal ratio Go-Me/S-N between the mild and moderate groups (p < 0.05) and the mild and severe groups (p < 0.05). However, no significant differences in Ricketts analysis factors were observed across OSA severity groups. Correlations between the Go-Me/S-N and Ricketts factors were identified in the mild and moderate groups but not in the severe group. The horizontal skeletal dimension Go-Me/S-N was strongly associated with OSA severity. Conclusions: The horizontal mandibular ratio Go-Me/S-N, independent of body shape, may offer a valuable morphological marker for differentiating OSA severity in non-obese males.